A pharmacogenetic study implicates SLC9a9 in multiple sclerosis disease activity. Issue 1 (14th May 2015) - Esposito, Federica; Sorosina, Melissa; Ottoboni, Linda; Lim, Elaine T.; Replogle, Joseph M.; Raj, Towfique; Brambilla, Paola; Liberatore, Giuseppe; Guaschino, Clara; Romeo, Marzia; Pertel, Thomas; Stankiewicz, James M.; et al.
<x xml:space="preserve">Abstract</x> Objective A proportion of multiple sclerosis (MS) patients experience disease activity despite treatment. The early identification of the most effective drug is critical to impact long‐term outcome and to move toward a personalized approach. The aim of the present study is to identify biomarkers for further clinical development and to yield insights into the pathophysiology of disease activity. Methods We performed a genome‐wide association study in interferon‐β (IFNβ)‐treated MS patients followed by validation in 3 independent cohorts. The role of the validated variant was examined in several RNA data sets, and the function of the presumed target gene was explored using an RNA interference approach in primary T cells in vitro. Results We found an association between rs9828519G and nonresponse to IFNβ (pdiscovery = 4.43 × 10−8) and confirmed it in a meta‐analysis across 3 replication data sets (preplication = 7.78 × 10−4). Only 1 gene is found in the linkage disequilibrium block containing rs9828519: SLC9A9. Exploring the function of this gene, we see that SLC9A9 mRNA expression is diminished in MS subjects who are more likely to have relapses. Moreover, SLC9A9 knockdown in T cells in vitro leads an increase in expression of IFNγ, which is a proinflammatory molecule. Interpretation This study identifies and validates the role of rs9828519, an intronic variant in SLC9A9, in IFNβ‐treated subjects, demonstrating a successful pharmacogenetic screen in MS. Functional characterization suggests that SLC9A9, an Na+‐H+ exchanger found in endosomes, appears to influence the differentiation of T cells to a proinflammatory fate and may have a broader role in MS disease activity, outside of IFNβ treatment. Ann Neurol 2015;78:115–127